The Role of Simulation Approach in Evaluating Foreign Language Communicative Skills of Philology Students - Olena Martynyuk (Pedagogical Discourse, 2013)
The article describes how to use the simulation approach to evaluate the foreign language communicative skills of philology students. The author characterizes the main evaluation strategies, defines the major factors to be considered during the communicative activity, gives the advantages and disadvantages of the simulation approach in the evaluation of students’ oral foreign language communicative skills.